Warranties in marine insurance - Soyer, Bariş (Cavendish, 2006)
Winner of the Cavendish Book Prize 2001 and the British Insurance Law Association Charitable Book Prize 2002. This book serves as an addition to the books devoted to the law of marine insurance. It includes an analysis of law reform, as well as a discussion of the proposals of the Australian Law Reform Commission.